2022
DOI: 10.1246/cl.210802
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of Biomass-derived γ-Valerolactone to Form 1,4-Pentanediol over Co/ZrO2 Catalyst

Abstract: Hydrogenation of γ-valerolactone (GVL) to form 1,4-pentanediol (1,4-PDO) was performed over Co/ZrO2 catalysts with a Co metal loading of 15 wt. %. The calcination of Co/ZrO2 at high temperatures significantly promoted the catalytic activity irrespective of the decrease in the specific surface area. The 750 °C-calcined Co/ZrO2 with Co2+ species exhibited a high catalytic performance: a GVL conversion of 86.1% with a 1,4-PDO selectivity of 97.2% was achieved at 165 °C under 5 MPa H2 pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The Co/ZrO 2 catalyst has been proven effective in the hydrogenation of γ-valerolactone to form 1,4-pentanediol. 20 However, we found that the Co/ZrO 2 catalyst was also effective for the direct hydrogenolysis of levulinic acid to form 1,4-pentanediol. In addition, the reaction results suggested that the hydrogenation of γ-valerolactone to form 1,4-pentanediol is the rate-determining step.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…The Co/ZrO 2 catalyst has been proven effective in the hydrogenation of γ-valerolactone to form 1,4-pentanediol. 20 However, we found that the Co/ZrO 2 catalyst was also effective for the direct hydrogenolysis of levulinic acid to form 1,4-pentanediol. In addition, the reaction results suggested that the hydrogenation of γ-valerolactone to form 1,4-pentanediol is the rate-determining step.…”
Section: Resultsmentioning
confidence: 87%
“…17,18 Among the products, 1,4-pentanediol is an attractive chemical, which can be used as a monomer in the production of polyesters, polyurethanes and alkyd resins. [19][20][21][22] Due to the important uses of 1,4-pentanediol, the catalytic conversion of levulinic acid or its derivers to form 1,4-pentanediol has attracted great research interest.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations